THE EFFECT OF PACKAGING TYPE ON THE PHYSICAL PROPERTIES OF HUSKED CORN AND CORN PEELED - Hadi Prastyo; Sulistyo SIDIK PURNOMO; Aisyah Hanifah (Talenta Publisher, 2026)
Sweet corn is a perishable horticultural commodity with a limited shelf life of approximately 2-3 days at room temperature. This study aimed to analyse the effect of packaging type and storage temperature on the physical and organoleptic properties of sweet corn husk and corn peeled forms. The research method used was a completely randomised design (CRD) factorial pattern with two main factors: storage temperature (room temperature and low temperature 3°C) and packaging type (no packaging, PP plastic, and hollow PP plastic). The observation parameters included organoleptic tests of aroma, colour, texture, and shelf life for 14 days. The results showed that the combination of low-temperature storage (3°C) and the use of polypropylene (PP) plastic packaging significantly extended the shelf life and maintained the physical quality of sweet corn. The aroma of corn could be maintained at its maximum (score 5) until the 8th day at cold temperatures. The use of hollow PP plastic for corn husk proved to be most effective in maintaining yellow colour stability until the 14th day. Meanwhile, for the texture parameter, the use of non-hollow PP plastic provided the best protection for shelled corn by suppressing the transpiration rate compared to no packaging. Overall, the integration of low temperature and PP plastic packaging is the most optimal preservation method to inhibit post-harvest quality deterioration of sweet corn. Keyword:Corn, Packaging Type, Storage Temperature, Pyhsical and Organoleptic Properties